2021
DOI: 10.1111/ijcp.14578
|View full text |Cite
|
Sign up to set email alerts
|

The association between apolipoprotein A‐1 plasma level and premature coronary artery disease: A systematic review and meta‐analysis

Abstract: Cardiovascular diseases (CVD) are the leading cause of death worldwide with nearly 18.6 million attributable deaths in 2019. The total prevalence of CVD has doubled during the last 30 years (271 million in 1990 vs 573 million in 2019) with a disability-adjusted life years of 34.4 million in 2019, worldwide. 1 Accordingly, shedding light on the pathophysiology and the contributing risk factors of coronary artery disease has been followed for many years till now. 2-4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Haji Aghajani M et al, in a review of seventeen case-control studies, found an association between Apo A 1 levels and premature coronary artery disease. However, the authors note the lack of good quality prospective cohort studies [ 40 ]. Erqou S et al, in a systematic review of thirty-six studies, found that people with smaller Apo A isoforms have an approximately 2-fold higher risk of coronary heart disease or ischemic stroke than those with larger proteins [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Haji Aghajani M et al, in a review of seventeen case-control studies, found an association between Apo A 1 levels and premature coronary artery disease. However, the authors note the lack of good quality prospective cohort studies [ 40 ]. Erqou S et al, in a systematic review of thirty-six studies, found that people with smaller Apo A isoforms have an approximately 2-fold higher risk of coronary heart disease or ischemic stroke than those with larger proteins [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our sample size was relatively small, and a larger population would be needed to confirm the association of HDL anti-inflammatory function with NAFLD. Our study included only male participants, because previous studies showed gender differences in lipid profile and HDL subfractions of different study populations [ 26 , 27 ]. Although we removed the confounding effect of gender, the results cannot be generalized to the whole population.…”
Section: Discussionmentioning
confidence: 99%
“…A lipoprotein that has shown a protective effect on inflammation, oxidation, angiogenesis and glucose homeostasis. For this reason, low HDL-C levels have been reported to increase CVR [30] Lipoprotein (a) (Lp-(a)) A protein that carries cholesterol in blood and has demonstrated to be an independent and CVR factor for the advancement of CVD [31] Apolipoprotein B (Apo B) A structural protein that transports very low-density lipoprotein (VLDL-C) and shown as a marker of atherogenic potential and CVR [32] Apolipoprotein A-I (Apo A-I) A primary component of HDL-C which has been shown to have an association with premature CVD [33] Paraoxonase-1 (PON1) A high-density lipoprotein-associated esterase that has been reported to have a direct and an indirect relationship with CVDs [34] Metabolic biomarkers…”
Section: Total Cholesterol (Tc)mentioning
confidence: 99%